ANALISIS HUKUM PENDAFTARAN TANAH TERHADAP TANAH KOMUNAL - salam, safrin; Nurcahyo, Edy; Pahlawan MP, H. Muhamad Rezky; Amrullah, Muhammad Salam (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2024)
Customary land rights are the highest form of land ownership under customary law, encompassing all land within a specific customary legal jurisdiction, jointly held by members of the indigenous community. The purpose of this research is to find a model for registering communal land in the land registration system and to determine the legal status of communal land in the land registration system. The research methodology used in this study is normative legal research, employing various approaches such as statutory approach and conceptual approach. The legal sources used include primary legal materials, secondary legal materials, and tertiary legal materials. The research findings indicate that the registration of communal land in the land registration system, both de facto and de jure, has been recognized and protected through two regulations that acknowledge the existence of communal land, namely Ministerial Regulation No. 10 of 2016 and the Complete Systematic Land Registration (PTSL) program. Essentially, communal land controlled by indigenous communities will be acknowledged through a decree issued by the regent/mayor/governor for the registered communal land at the local National Land Agency (BPN) office. However, the legal status of communal land in the Land Registration System shows that communal land is not included in the rights to land as regulated in Government Regulation No. 24 of 1997 concerning land registration. Therefore, a revision of the land registration regulation is necessary to ensure the legal certainty of communal land controlled by indigenous communities